Automated Event-Triggered GUI Testing and Bug Reproduction for NonAndroid Applications - Anit Thomas M; Chinchu Krishna S (International Journal of Innovation in Enterprise System, 2021)
Today’s mobile gadgets are seamlessly incorporating innovative features demanded by the users.Most often, the applications contain bugs or functionality issues reported by the customers. Thedevelopers are responsible for reproducing such reported bugs, which are written in naturallanguages. Reproducing bugs from bug reports make the bug resolution inefficient. Nowadays,various methods are adopted to reproduce crash reports for android applications. But bugreproduction for non-android applications is still a challenging task. This paper proposes a novelapproach that is capable of doing bug reproduction from bug reports to help the developers to solvethe functionality issues of non-android applications in an automated manner. This approach uses aUI tester called the GUI engine, which is an excel sheet. The use cases which are to be tested canbe filled in the GUI engine. All the use cases are to be filled based on a particular syntax. For thatpurpose, the developer can make use of a set of yaml files containing all the GUI information forall the screens of the application under test. The use cases are executed in the GUI engine andconclusions are made based on the test result. The GUI engine displays two colors green and redshowing the working and failing of GUI components of the application under test. So that thedeveloper can easily identify the failing components and take actions accordingly. The test hasbeen done with more than 1000 test cases for one region and the result shows that almost all GUIcomponents work for this method except for animation. It has tested for software developed forUS, Europe, and German regions. Also, the proposed method is found to be much faster andefficient than the existing as well as manual testing methods.